Pelatihan Pengolahan Produk Lokal Buah Nanas Menjadi Nata de pina sebagai Upaya Inovasi Produk Unggulan Siswa SMK - Mar’atus Sholihah; Eva Nurul Malahayati; Supriyono (Jurnal SOLMA, 2021)
Background: Vocational High School (SMK) has an essential role in printing a workforce that can produce superior products. The limited facilities of production infrastructure and the turtle of experts who accompany it become an obstacle in its implementation. This community service activity aims to provide training in processing local products superior to Blitar and its surroundings, namely pineapple and coconut water in SMKI An-Harul Ulum Kademangan so that products are produced in the form of nata de pina that are quality, worth consuming, and have selling value. Method: Devotional activities are carried out by debriefing materials and mentoring about local pineapple product processing techniques and entrepreneurs. The training site is centred in a laboratory with 20 students. Results: The results of this devotion can improve students' skills in the process of processing local pineapple products as nata de pina and improve students' ability to be entrepreneurial, as shown by the results of student response to local pineapple product processing training activities at SMKI Anharul Ulum Kademangan is quite good with reaction level indicators of 83%, learning level 79%, behaviour level 80%, and the resulting level is 80%. Conclusion: This pineapple and entrepreneur local product processing training activity can improve students' skills in the process of processing local products in this case the manufacture of nata de pina and improve students' ability in entrepreneurship.